2021
DOI: 10.1111/joor.13283
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Temporomandibular Disorder Pain: A critical review of differentiating factors and predictors of acute to chronic pain transition

Abstract: Temporomandibular disorders (TMD) are a group of musculoskeletal disorders which affect the muscles of mastication, the temporomandibular joints, and/or associated structures. 4 Studies demostrate several biopsychosocial factors associated with the risk of TMD pain. [5][6][7][8][9][10][11][12] Persistence of TMD pain is common; about one-third to half of TMD patients continue to suffer TMD pain after followup. [13][14][15] Thus, it is crucial to prevent acute TMD pain from becoming chronic, which is more chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
1
11
0
1
Order By: Relevance
“…(4) The absence of history of TMD treatment and masticatory pain in the last 30 days were considered indicators of acute (or first onset) myogenous TMD but the present study lacks of reliable criteria to differentiate acute and chronic pain patients (e.g. International Association for the Study of Pain chronic pain definition [45]); this is important since although transition from acute to chronic TMD pain is common [46], acute TMD typically represent simpler cases that can be managed by a single clinician with self-care, but chronic TMD are more complex and should be managed interdisciplinary [34].…”
Section: Discussionmentioning
confidence: 99%
“…(4) The absence of history of TMD treatment and masticatory pain in the last 30 days were considered indicators of acute (or first onset) myogenous TMD but the present study lacks of reliable criteria to differentiate acute and chronic pain patients (e.g. International Association for the Study of Pain chronic pain definition [45]); this is important since although transition from acute to chronic TMD pain is common [46], acute TMD typically represent simpler cases that can be managed by a single clinician with self-care, but chronic TMD are more complex and should be managed interdisciplinary [34].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have investigated differences between patients with acute and chronic TMD pain. Sabsoob and coworkers in a critical review including seven studies found no significant difference regarding age, race, gender and socioeconomical status between the groups ( 33 ). However, one of the included studies reported that chronic TMD pain was more prevalent in females than in males ( 34 ).…”
Section: The Transition From Acute To Chronic Tmd Painmentioning
confidence: 98%
“…A recent critical review found a few differences between acute and chronic TMD. 20 Nguyen et al found that coexisting pain beyond orofacial areas (e.g., facial pain, neck, abdomen) was more common among patients with chronic pain–related TMDs and only participants with chronic pain–related TMDs presented certain comorbidities (e.g., fibromyalgia, chronic fatigue syndrome). 21 A borderline difference was found with disability score ( P = 0.07) between the two TMD pain groups.…”
Section: Introductionmentioning
confidence: 99%